ATENÇÃO À SAÚDE DO IDOSO EM DOMICÍLIO: A VISÃO DE ACADÊMICOS DE ENFERMAGEM NO PROJETO DE ATENÇÃO AO IDOSO – P.A.I. - Manchini, Tacinara P.; Coracini, Annekelly; Mayer, Bárbara L. D.; Bonfada, Sonia T. (Salão do Conhecimento, 2013)
Resumo